Analisis Strategi Pemasaran dalam Mempertahankan Loyalitas Konsumen Perspektif Manajemen Bisnis Syariah pada Warung Joyoboyo Kota Bukittinggi - Muhammad Naufal; Muhammad Rais (ARZUSIN, 2026)
Marketing strategies in culinary micro, small, and medium enterprises (MSMEs) have become a focus in various previous studies; however, research that specifically discusses marketing strategies in maintaining consumer loyalty based on the perspective of Islamic business management remains limited. This study aims to analyze the marketing strategies implemented by Warung Joyoboyo in maintaining consumer loyalty. This study employed a qualitative approach with a case study design. The research participants were consumers of Warung Joyoboyo selected through the purposive sampling technique. Data were collected through interviews, observation, and documentation and were then analyzed using qualitative descriptive techniques through the stages of data reduction, data presentation, and conclusion drawing. The results show that marketing strategies through the elements of the marketing mix, which include product, price, place, and promotion, play a role in shaping consumer loyalty. Product quality, affordable prices, strategic location, and word-of-mouth promotion are the main factors that encourage repeat purchases and recommendations to other consumers. However, the level of consumer loyalty shows variation influenced by individual experiences and preferences. These findings contribute to the development of marketing studies, particularly the integration of the marketing mix concept with the perspective of Islamic business management, and broaden understanding of marketing strategies in culinary MSMEs. The conclusion of the study emphasizes that the implementation of effective and ethical marketing strategies plays an important role in increasing consumer loyalty. The practical implication is that MSME actors need to maintain product quality and service consistency so that consumer loyalty can be sustained.